Silence, Discipline and Student Bodies - Latremouille, Jodi Marie (Journal of the Canadian Association for Curriculum Studies, 2018)
In this ecological poetic inquiry, I contemplate a curriculum of silence, discipline and student bodies. As I seek to work through and against the entrenched-knowings of school and schooling in these ecologically urgent times, I contemplate how children’s bodies are disciplined, how the voices of nature are silenced, how dominance rears its head through the myths of competition, progress and human supremacy. The cluster of poems is a consideration of some of the ways in which bells, security screening systems, silent lunchrooms, dead-lines, and all of the so-called “practical necessities” of schools, serve to silence and marginalize the voices, beings and bodies implicated in the industrial-powerful places and ecologically barren times of education. I ask, what wild, young-old, creaking, sleeping voices, beings and bodies need to be considered in our curriculum encounters? In response to David Geoffrey Smith’s (2014) call for educators to “reimagine new, wiser, human possibilities” (p. 1), I consider how educators may encounter ecological possibilities for a curriculum of living.